A Study on Muslim Younger Generation’s Behavioral Intentions towards Purchasing of Halal Cosmetic Products in Pakistan - Nawaz, Muhammad Shah; Mahmud, Mohd Sadad; Nasir, Muhammad; Mansha, Muhammad Imran; Sabir, Irfan; Majid, Muhammad Bilal; Nawaz, Farooq (The journal of contemporary issues in business and government, 2021)
The purpose of this paper is to study the young Muslim consumer’s behavioural intentions to purchase halal cosmetic products in Pakistan. There are three independent variables namely consumer innovativeness, product characteristic, perceived behavioural control which effect the dependent variable of consumer behavioural intention. Theory of planned buying behaviour and diffusion of innovation is used as supportive theories. Data were collected from 370 young Muslim consumers in Pakistan. Self-administered questionnaires with 10-point interval scales were used. In this study, a quantitative research method was employed to examine hypotheses. The data were analyzed by using the (SEM) technique. Findings of the study show that perceived behavioural control, product characteristics and consumer innovativeness has a significant effect on halal behavioural intention. The findings can benefit the halal cosmetic companies that young Muslim generation has positive behaviour inactions to purchase the halal cosmetic product. The associations set up in this study constitute a significant addition to the current knowledge bases. The findings contribute to halal cosmetic research by illustrating the young generation of Muslim consumers behaviour for purchase halal cosmetic product.